Photodynamic therapy of the experimental tumors of different morphological types with liposomal boronated chlorin е6 - O. B. Abramova; V. V. Drozhzhina; T. P. Churikova; E. A. Kozlovtceva; L. M. Arkhipova; M. A. Kaplan; S. A. Ivanov; A. D. Kaprin (Biomedical Photonics)
The article summarizes the results of studies of the effectiveness of photodynamic therapy using a new domestic photosensitizer liposomal borated chlorin e6 (LBC) after its parenteral administration (intraperitoneal and intravenous). Antitumor efficacy was evaluated in rats with M-1 sarcoma and PC-1 alveolar liver cancer and mice with B16 melanoma and Ehrlich’s carcinoma, which were transplanted subcutaneously into the thigh area of the animals. The aim of the study was to determine the optimal regimes of photodynamic therapy that would allow achieving the maximum antitumor effect up to 21 days after the photodynamic therapy. The therapy was carried out under the control of the accumulation of the photosensitizer in the tumor and surrounding tissues of the thigh by selecting the doses of the drug and the parameters of laser radiation (energy density and power density). The effectiveness of therapy was assessed by the inhibition of tumor growth, by the percentage of animals with complete tumor regression, by the absolute growth rate in animals with continued tumor growth compared to controls. The results of our studies have shown that the domestic photosensitizer liposomal borated chlorin e6 has high antitumor activity in vivo. In an experimental study of the photosensitizer under certain PDT modes, the maximum antitumor effect (complete tumor regression in 100% of animals) was obtained up to 21 days after PDT in all tumor models used.